Creation of a book-museum in a library: principles, problems and possibilities - Kalvik, Kal (Knygotyra, 2003)
Museum is an institution in which the heritage of culture and nature is collected, preserved, researched and exhibited. While museums preserve mainly objects, libraries and archives have similar functions depositing publications and documents. In Estonia museum work as a science field was initiated at the beginning of the 19th century due to the establishment of the Estonian National Museum in Tartu. Collections with the cultural significance for Estonia are registered in separate databases – archives, museums and libraries do not have a common database. In order to coordinate and modernize museum work at the level of state the Museum Law was passed in the 1990s and the Museum Council as well as the Estonian Council of Preservation of Cultural Heritage in Libraries, Archives and Museums have been formed by the Ministry of Culture. In 1999 the question of museum reform was brought up due to several problems. In 2000 two development programmes – one for museums and the other for libraries – were introduced by the Ministry of Culture to the specialists. Consequently, the Estonian Academic Library will be united with Tallinn University, the creation of which has not yet been completed. The debate about the meaning of the term "book-museum" has lasted for decades in the whole world by now. The majority of book researchers in the world share the principle that book-museum must characterize the mental and material essence of the book through time. The first plan of book-museum in Estonia dates back to 1940. In the development of museologic thought theoretical-synthesizing museology began to develop in the 1970–1980s side by side with empirical-descriptive museography. Book as a museum exhibit is handled as a culture-sign with its structural elements and semiotic connections. While framing the project of the book- and library-museum of the Estonian Academic Library, the following questions should be answered: why and to whom we create the exposition and how to do it professionally? Since Tallinn University is still in the process of development, it is quite difficult for the library to define the exact essence of book-museum as the ideology of exhibition depends, besides collections, also on the target group, the size of exhibition area and technical possibilities. Any exposition is based on collections. The Estonian Academic Library has the collections of Baltica and Foreign-Estonian literature which enable to organize both permanent expositions as well as long-term thematic exhibitions. The exposition in modern museum is completed in the cooperation of museologist, producer, architect, artist, light- and sound-technician in order to provide the spectator with as versatile experience as possible. The mediation of extra information by means of updated multimedia equipment definitely enriches the exhibition. Modern museum is unable to operate successfully while being self-absorbed. In order to introduce book culture in a variety of forms, cooperation with various institutions are needed. Cultural heritage requires state preserve politics which defines the responsibilities of institutions in different spheres and establishes preconditions for completing them.